Reliability Assessment and Maintenance Strategy of Retreaded Tires in Commercial Aircraft: A Study on Usage Effectiveness - Vera Yuliana Agustini; muhammad Andi Nova; Budhi Muliawan Suyitno; Fathan Mubina Dewadi; Mohamad Alif Dzulfiqar (Institut Teknologi Dirgantara Adisutjipto, 2025)
Aircraft has become a mode of transportation experiencing a significant increase in demand in line with global mobility growth, including in Indonesia. The rise in flight cycles has consequently increased the need for reliable and cost-efficient aircraft tires. This study aims to analyze the reliability and failure patterns of retreaded aircraft tires using the two-parameter Weibull distribution method (β and η). Data were obtained from operational records of commercial aircraft and analyzed to determine the Mean Time To Failure (MTTF), failure modes, and maintenance strategy effectiveness. The results indicate that the highest reliability occurs in the third retreading cycle, with a reliability value of 0.99 and an MTTF of 180 flight cycles. The dominant failure mode is identified as wear-out failure, suggesting that preventive maintenance through regular inspection and replacement is the most effective approach. These findings provide a scientific basis for improving operational safety and efficiency while supporting the implementation of sustainable maintenance practices in the national aviation industry.